2016
DOI: 10.1111/cdev.12615
|View full text |Cite
|
Sign up to set email alerts
|

English Language Proficiency and Early School Attainment Among Children Learning English as an Additional Language

Abstract: Children learning English as an additional language (EAL) often experience lower academic attainment than monolingual peers. In this study, teachers provided ratings of English language proficiency and social, emotional, and behavioral functioning for 782 children with EAL and 6,485 monolingual children in reception year (ages 4–5). Academic attainment was assessed in reception and Year 2 (ages 6–7). Relative to monolingual peers with comparable English language proficiency, children with EAL displayed fewer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 47 publications
(105 reference statements)
1
33
0
Order By: Relevance
“…Receptive and expressive language skills are vital for scholastic development and are key in the identification of learning difficulties, as language difficulties are widely associated with increased risk of poor educational outcomes (Tomblin, 2008; Peterson et al, 2009). For example, vocabulary knowledge is closely related to children's mathematics skills (Lee et al, 2004), and language proficiency is closely associated with academic attainment in the UK (Whiteside et al, 2016), and in low-income countries (Pretorius and Mampuru, 2007). Similarly, written language skills, especially literacy, are considered key building blocks on which later learning is dependent (e.g., Cunningham and Stanovich, 1997; Duncan et al, 2007; Sparks et al, 2014), so inclusion of tasks assessing spoken and written language processing would enhance the scope of this new cross-cultural touch screen assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Receptive and expressive language skills are vital for scholastic development and are key in the identification of learning difficulties, as language difficulties are widely associated with increased risk of poor educational outcomes (Tomblin, 2008; Peterson et al, 2009). For example, vocabulary knowledge is closely related to children's mathematics skills (Lee et al, 2004), and language proficiency is closely associated with academic attainment in the UK (Whiteside et al, 2016), and in low-income countries (Pretorius and Mampuru, 2007). Similarly, written language skills, especially literacy, are considered key building blocks on which later learning is dependent (e.g., Cunningham and Stanovich, 1997; Duncan et al, 2007; Sparks et al, 2014), so inclusion of tasks assessing spoken and written language processing would enhance the scope of this new cross-cultural touch screen assessment tool.…”
Section: Discussionmentioning
confidence: 99%
“…Initial strata identified children who were reported as having ‘no phrase speech’ (NPS, n = 89, 1.2%), those attending special schools for severe learning disabilities ( n = 31, including 19 NPS, 0.4%) and those for whom English was an additional language ( n = 782, 10.7%, including 27 NPS). No Phrase Speech (NPS) was recorded when teachers provided a negative response to the question ‘is the child combining words into phrases or sentences?’ Children in special schools at study intake were excluded, while children with English as an additional language were invited to a different study and their data are not reported here (Whiteside, Gooch, & Norbury, ). All additional children with NPS ( n = 48) were invited for in‐depth assessment.…”
Section: Methodsmentioning
confidence: 99%
“…No Phrase Speech (NPS) was recorded when teachers provided a negative response to the question 'is the child combining words into phrases or sentences?' Children in special schools at study intake were excluded, while children with English as an additional language were invited to a different study and their data are not reported here (Whiteside, Gooch, & Norbury, 2017). All additional children with NPS (n = 48) were invited for in-depth assessment.…”
Section: Methodsmentioning
confidence: 99%
“…It is perhaps not surprising that it can pose particular challenges for children who are learning English as an additional language (EAL) while using a minority language at home (Spencer & Wagner, 2017). Since EAL children's English proficiency is highly predictive of their educational success and personal well-being (Strand & Demie, 2005;Strand & Hessel, 2018;Whiteside, Gooch, & Norbury, 2017), it is important to understand these challenges. EAL learners often lag behind monolinguals in reading comprehension and this is linked to relative deficits in vocabulary size and depth, but not reading fluency (Bowyer-Crane, Fricke, Schaefer, Lervåg, & Hulme, 2017;D'Angiulli, Siegel, & Serra, 2001;Hessel & Murphy, 2019;Lesaux, Rupp, & Siegel, 2007;Spätgens & Schoonen, 2018;Spencer & Wagner, 2017;Verhoeven, 2000).…”
Section: Comprehension Monitoring During Reading: An Eye-tracking Stumentioning
confidence: 99%